Rejoicing in the works of the Lord : beauty in the Franciscan tradition - Ingham, Mary Beth, 1951- (St. Bonaventure, N.Y. : Franciscan Institute Publications, 2009)
The special focus of this study is the appreciation of beauty in the writing of two great theorists of the tradition, Bonaventure of Bagnoregio and John Duns Scotus.
Franciscans and beauty -- The beauty of creation -- The beauty of the human heart -- The Franciscan path of transformation into beauty -- Toward a Franciscan aesthetic.
Includes bibliographical references (pages 75-78).
Print version record.
Keywords: Aesthetics -- Religious aspects -- Catholic Church; Aesthetics -- Religious aspects -- Catholic Church; Franciscans -- Theology; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; Electronic books